Pengaruh Kualitas Fisik Udara terhadap Kejadian Sick Building Syndrome pada Pegawai Gedung Menara UMI Makassar - Amaliah Natsir; Sainah, Sainah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Over the past two decades, the construction of high-rise buildings with closed ventilation systems has become increasingly common in various countries. Most of these buildings rely on artificial ventilation systems using Air Conditioners (AC). If not properly maintained, AC units can become a source of indoor air pollution, ultimately reducing air quality and triggering health issues. One of the health disorders associated with indoor air quality is Sick Building Syndrome (SBS), which is the focus of this study. SBS is a condition caused by exposure to pollution in enclosed spaces and is closely related to environmental factors, particularly indoor air quality. This study employed data collection methods through questionnaires and measurements of physical air parameters, including temperature, humidity, airflow velocity, and lighting. The study population consisted of 157 individuals, with 47 participants selected using the purposive sampling technique. Bivariate analysis was conducted using the chi-square test, while multivariate analysis was performed using multiple linear regression. The results showed no significant relationship between temperature and airflow velocity with the occurrence of SBS. However, humidity and lighting were significantly associated with SBS. Among these factors, lighting was identified as the most influential variable in the occurrence of SBS, confirming the research hypothesis. As a recommendation, employees are encouraged to maintain their physical well-being and practice relaxation techniques when experiencing SBS symptoms. Additionally, building management is advised to regularly monitor indoor air quality to prevent the adverse effects of SBS